Elevations in D-dimer levels in patients with Plasmodium infections: a systematic review and meta-analysis - Suriyan Sukati; Kwuntida Uthaisar Kotepui; Frederick Ramirez Masangkay; Ching-Ping Tseng; Aongart Mahittikorn; Nsoh Godwin Anabire; Polrat Wilairatana; Kinley Wangdi; Hideyuki J Majima; Apiporn Thinkhamrop Suwannatrai; Wiyada Kwanhian Klangbud; Wanida Mala; et al. (Scientific Reports)
Abstract D-dimer, a byproduct of cross-linked fibrin degradation, arises during the fibrinolysis process, breaking down blood clots in circulation. This systematic review and meta-analysis aimed to synthesize evidence of D-dimer alteration in people with malaria, including variations in disease severity. The systematic review was registered in PROSPERO with registration number CRD42024528245. Searches were performed in EMBASE, Scopus, MEDLINE, PubMed, Nursing & Allied Health Premium, and Journals@Ovid on March 25, 2024, to identify original studies that reported D-dimer in patients with Plasmodium infections. The methodological quality of the included studies was assessed using the Joanna Briggs Institute critical appraisal tools. Thematic synthesis and meta-analysis were carried out to synthesize the findings of the included studies. A total of 24 studies were included in the review out of 1,115 records identified. According to the evaluated studies, patients with Plasmodium infections had higher D-dimer levels. A meta-analytic evaluation of D-dimer levels between patients with and without Plasmodium infections revealed a significant elevation of D-dimer in patients with infection, with high heterogeneity (SMD = 2.11, 95% CI = 0.59; 3.64, P = 0.007, I² = 98%, 6 studies, 1,418 participants, random-effects model). However, no significant alterations in D-dimer levels were observed following the comparison between patients with severe and uncomplicated malaria, also with high heterogeneity (SMD = 2.54, 95% CI = -1.60; 6.68, P = 0.23, I² = 99%, 3 studies, 595 participants). The findings suggested that malaria patients have significantly higher D-dimer levels compared to non-malarial individuals. However, there was no significant difference in D-dimer levels between severe and uncomplicated malaria cases. These results highlight the potential of D-dimer as a biomarker for Plasmodium infections, but its clinical utility requires further validation. Future studies should prioritize standardizing D-dimer measurement methods, including assay types, threshold values, and sample types, to ensure consistent and reliable application in clinical settings. Additionally, large, multicentric cohorts are needed to establish robust guidelines for incorporating D-dimer into malaria management practices. Further research should also explore the role of D-dimer in the pathogenesis of Plasmodium infections to deepen our understanding of their clinical significance.